Enforceability, compliance and justiciability of social rights in Mexico-2022 - Ramírez Izazaga, Cinthia (2023)
Social rights are essential for every human being, these rights intervene in the living conditions of people and guarantee their dignity; therefore, their absence generates adverse life situations, violating human dignity. In order for social rights to be effective, it is necessary to have the effective intervention of the State, since it is the State that must provide the optimal tools and conditions for everyone to fully enjoy their social rights; however, the Mexican State has not always provided due attention, which generates vulnerability in people's lives. The importance of social rights lies in the fact that they are essential to ensure human dignity; therefore, the action of the State is defining to ensure them. As expressed in previous lines, it is important to analyze the situation of social rights in Mexico; as well as its enforceability, compliance and justiciability. To carry out the present investigation, the inductive method was used, due to its purpose, the work presented is descriptive, interpretive and socio-legal; using the following techniques: collection of statistical data, legislation, books, magazines and others. Among the main conclusions, it was found that the actions of the Mexican State do not satisfy the social needs of the population in a timely manner.